Cherry Blossoms - Dorrie, Doris (Germany, 2008)
When Trudi learns that her husband Rudi is dangerously ill, she suggests visiting their children in Berlin without telling him the truth. As Franzi and Karl don't care much about their parents, Trudi and Rudi go to the Baltic Sea, where Trudi suddenly dies. Rudi is thrown out of gear, even more when he learns that his wife wanted to live a totally different life in Japan...
Verzio Film Festival Submission
Keywords: Documentary films